Evaluation of Double Taxation Agreements (DTAs) in Preventing Double Taxation in the Digital Economy Era - Loso Judijanto (PT. Anagata Sembagi Education, 2025)
This study analyzes the determinants of tax aggressiveness in public companies by examining the interaction between firm-level financial characteristics, corporate governance structures, and institutional environments. Employing a quantitative panel-data design, the study evaluates 84 firm-year observations from Indonesia and Malaysia, using fixed-effects and random-effects models to test how leverage, profitability, firm size, ownership concentration, and governance quality influence tax aggressiveness measured through cash effective tax rates and book-tax differences. The findings indicate that higher leverage and profitability significantly increase tax aggressiveness, while stronger board independence and higher audit quality reduce it. Institutional factors, including regulatory enforcement, legal clarity, and audit intensity, moderate firm behavior and shape the extent of aggressive tax practices. The results reveal that tax aggressiveness is not driven by isolated variables but emerges from combined financial incentives and institutional opportunities. Firms in weaker regulatory environments exhibit higher aggressiveness, demonstrating the role of institutional quality in shaping compliance. The study concludes that reducing tax aggressiveness requires comprehensive reforms that integrate improvements in corporate governance with strengthened enforcement and regulatory clarity. The findings contribute to the literature by offering a multidimensional analysis that bridges firm-level and institutional determinants of tax behavior